Expression of peach sucrose transporters in heterologous systems points out their different physiological role. (September 2015) - Zanon, Laura; Falchi, Rachele; Hackel, Aleksandra; Kühn, Christina; Vizzotto, Giannina
Highlights: We demonstrate the functionality of PpSUT1 and PpSUT4 peach sucrose transporters. PpSUT1 and PpSUT4 localise at plasma membrane and tonoplast, respectively. PpSUT2 failed to give clear indication about its localisation. A protein–protein interaction post-transcriptionally regulates the transporters. We model peach sucrose transporters role in whole plant carbohydrates partitioning. Abstract: Sucrose is the major phloem-translocated component in a number of economically important plant species. The comprehension of the mechanisms involved in sucrose transport in peach fruit appears particularly relevant, since the accumulation of this sugar, during ripening, is crucial for the growth and quality of the fruit. Here, we report the functional characterisation and subcellular localisation of three sucrose transporters (PpSUT1, PpSUT2, PpSUT4) in peach, and we formulate novel hypotheses about their role in accumulation of sugar. We provide evidence, about the capability of both PpSUT1 and PpSUT4, expressed in mutant yeast strains to transport sucrose. The functionality of PpSUT1 at the plasma membrane, and of PpSUT4 at the tonoplast, has been demonstrated. On the other hand, the functionality of PpSUT2 was not confirmed: this protein is unable to complement two sucrose uptake-deficient mutant yeast strains. Our results corroborate the hypotheses that PpSUT1 partakes in phloem loading in leaves, and PpSUT4 sustains cell metabolism by regulating sucrose efflux from the vacuole.